(untitled) (Fiep Bulletin - online, 2013)
This paper is intended to identify the importance of changes in the working process in a sector of forestry on a company in the region of Santa Catarina. The research was qualitative and quantitative, the method of assessing the workstation met the ergonomics criteria, being analyzed, the demand for labor and labor activity, to this item, it was applied ergonomic check-list for the following evaluations: the condition of ergonomic method of work, the biomechanics occupational condition, the condition of ergonomic workstation, the condition of the degree of repetitiveness of the task, the activity waste energy via Lehman method and the analysis of the worker posture through the templates Couto and RULA. Among the resources used and of fundamental importance to ergonomics, the images through pictures, contributed to the analysis of data, in the anthropometrics evaluation it was used measure tape where average values were obtained in the sector of the population assessed, taking into consideration as a theoretical basis the German Standard called Deutsches Institut Für Normung (DIN 33,402), this standard provides points of reference in assessing the heights and lengths of work. The final results, after the Labor Ergonomics Analysis (AET) identified the ergonomic hazards and highlighted the improvements needed, thus avoiding accidents in Forestry, optimizing the labor work, helping to protect the employee and prioritizing the importance of ergonomic study in any job.